2018
DOI: 10.32861/journal.7.2018.48.134.139
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Behavioural Rehearsal Technique on Test Anxiety Among Secondary School Students in Orlu Lga, Imo State, Nigeria

Abstract: Latin is the dominant donor language to most modern European languages, which were in turn influential donor languages to Malay due to colonization between the 16th and 20th centuries. This study conducted a vocabulary survey to assess the benefits of using word categories of frequently used English vocabulary of Latin and Greek origins and their Malay equivalents for learning Malay as a foreign language. The Oxford 3000 list served as the primary reference of high-frequency English words and their Malay equiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…According to Hassanbeigi et al (2011), teaching study skills to university students can play a vital role in improving students' academic performance. Similar findings by Nwokolo et al (2018) indicated that behaviour rehearsal techniques involving study skills training and testtaking skills training effectively reduced students' test anxiety. Introducing the UED102 module at the beginning of the Diploma program was seen as a method of instilling positive behaviours in the student to perform well academically.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…According to Hassanbeigi et al (2011), teaching study skills to university students can play a vital role in improving students' academic performance. Similar findings by Nwokolo et al (2018) indicated that behaviour rehearsal techniques involving study skills training and testtaking skills training effectively reduced students' test anxiety. Introducing the UED102 module at the beginning of the Diploma program was seen as a method of instilling positive behaviours in the student to perform well academically.…”
Section: Discussionsupporting
confidence: 53%
“…Therefore, they proposed that appropriate psycho-educational intervention be conducted to improve academic performance. Nwokolo et al (2018) indicated that behaviour rehearsal techniques involving study skills training and test-taking skills training effectively reduced secondary school students' test anxiety. Khalaila (2015) suggested psycho-educational intervention to improve the students' performance, such as giving more attention to motivational factors (e.g., self-concept and motivation) and reducing the negative impact of situational factors (e.g., test anxiety).…”
Section: Test Strategies and Test Anxietymentioning
confidence: 99%
“…One of the earliest test anxiety scales was developed by Spielberger (1980). It has been frequently used in Nigeria to assess the prevalence of test anxiety among Nigerian students as well as the relationships between test anxiety and other important psychosocial variables (Anyamele et al, 2016;Galle et al, 2020;Nwokolo et al, 2017;Nwosu et al, 2016Nwosu et al, , 2017Okoli & Nnoli, 2008). Additionally, several of these research have shown how test anxiety levels vary between male and female students.…”
Section: Introductionmentioning
confidence: 99%